Experimental medicine study with stabilised native-like HIV-1 Env immunogens drives long-term antibody responses, but lacks neutralising breadthResearch in context - Katrina M. Pollock; Hannah M. Cheeseman; Leon R. McFarlane; Suzanne Day; Monica Tolazzi; Hannah L. Turner; Jennifer Joypooranachandran; Katsiaryna Shramko; Stefania Dispinseri; Philipp Mundsperger; Ilja Bontjer; Nana-Marie Lemm; et al. (EBioMedicine)
Summary: Background: We report findings from an experimental medicine study of rationally designed prefusion stabilised native-like HIV envelope glycoprotein (Env) immunogens, representative of global circulating strains, delivered by sequential intramuscular injection. Methods: Healthy adult volunteers were enrolled into one of five groups (A to E) each receiving a different schedule of one of two consensus Env immunogens (ConM SOSIP, ConS UFO, either unmodified or stabilised by chemical cross-linking, followed by a boost with two mosaic Env immunogens (Mos3.1 and Mos3.2). All immunogens were co-formulated with liposomal Monophosphoryl-Lipid A (MPLA) adjuvant, and volunteers were followed up for 28 days post final Mosaic booster injection. Participants gave written informed consent to join the study. The study is registered on ClinicalTrials.gov ID NCT03816137. Findings: Fifty-one participants (men n = 23 and women n = 28) aged 18–55 were enrolled. The seroconversion rate against Env was 100% with all participants having measurable anti-Env IgG antibodies after their second injection and throughout the study. Neutralisation was detected against the ConM pseudovirus in sera of those who had received both ConM and ConS immunogens. However, this activity was limited in breadth and was neither boosted nor broadened in those receiving the Mos3.1 and Mos3.2 immunogens. Neutralising antibody function correlated with binding to V1/V3 and V5 epitopes and peaked after the third injection. Interpretation: Rationally designed prefusion-stabilised native-like Env trimers are robustly immunogenic in a prime-boost schedule. When given alone they are insufficient to induce neutralising antibody titres of significant breadth, but they represent potentially valuable polishing immunogens after germline-targeting. Funding: European Aids Vaccine initiative (EAVI2020) received funding from EU Horizon 2020, grant number 681137. Structural studies were supported by the Bill and Melinda Gates Foundation (INV-002916).